2013
DOI: 10.3109/09273948.2013.806989
|View full text |Cite
|
Sign up to set email alerts
|

Improved Retinal Ganglion Cell Survival through Retinal Microglia Suppression by a Chinese Herb Extract, Triptolide, in the DBA/2J Mouse Model of Glaucoma

Abstract: To investigate the changes in retinal microglia and retinal ganglion cell (RGC) survival after long-term administration of a Chinese herb extract, triptolide, in a DBA/2J mice. DBA/2J mice (n = 96) were administered triptolide (n = 48) 25 µg/kg or vehicle (n = 48) and were judged at 7, 9, 11 months of age. Long-term triptolide treatment tended to attenuate the anterior segment pathology in experimental group, though intraocular pressure was not significantly different between the two groups. In the experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The progressive degeneration of retinal ganglion cells (RGCs) and sustained loss of the visual field are its remarkable characteristics [12]. Recent studies suggested that activated microglia participate in the pathological course of glaucomatous optic injury with adverse consequences [13], [14], and reduced microglial activation was associated with alleviating optic nerve and retinal neurodegeneration [15].…”
Section: Introductionmentioning
confidence: 99%
“…The progressive degeneration of retinal ganglion cells (RGCs) and sustained loss of the visual field are its remarkable characteristics [12]. Recent studies suggested that activated microglia participate in the pathological course of glaucomatous optic injury with adverse consequences [13], [14], and reduced microglial activation was associated with alleviating optic nerve and retinal neurodegeneration [15].…”
Section: Introductionmentioning
confidence: 99%
“…the OS, OPL, IPL, and GCL-NFL. Most studies of microglial activation over time after OHT have involved a DBA/2 J mouse model of inherited glaucoma [34][35][36][37][38] . Other studies have relied on rat glaucoma models, in which OHT is induced differently than in our model 21,[39][40][41][42][43][44][45] .…”
Section: Discussionmentioning
confidence: 99%
“…Protective effects of triptolide on dopaminergic neurons damage were mediated by the inhibition of proinflammatory mediators from activated microglia, as demonstrated in MPP+-induced hemiparkinsonian rats [67], with an improvement in behavioral disabilities. Additionally, preclinical glaucoma studies have demonstrated that this diterpenoid improved RGC survival through the suppression of microglia activation and proliferation in glaucoma rat models [68,69]. Besides having protective effects via the microglia, triptolide exhibited in vitro neurotrophic activity via stimulation of the production and release of NGF in astrocytes [70].…”
Section: Diterpenoids and Triterpenoids As Potential Neuroprotective mentioning
confidence: 99%